The Influence of Organizational Support on Employee Job Performance at PT. Astra Daihatsu Alauddin - Muhammad Ansar; Yusuf Alfian Rendra Anggoro; Firman Syah (Economos : Jurnal Ekonomi dan Bisnis, 2025)
Employee performance is a critical determinant of organizational success and is strongly influenced by the extent of organizational support. Perceived Organizational Support (POS) has received significant attention in organizational behavior research, as it represents employees’ perceptions of the extent to which the organization values their contributions and cares about their well-being. This study aims to investigate the effect of POS on employee performance at PT Astra Daihatsu Alauddin. A quantitative research design was employed, with data collected through questionnaires distributed to employees. Responses were measured using a Likert scale and analyzed with the Statistical Package for the Social Sciences (SPSS) version 21 to examine the relationships between variables. The findings indicate that organizational support has a positive and significant impact on employee performance. Employees who perceive higher levels of support from the organization demonstrate greater job achievement, stronger commitment, and increased productivity. These results highlight the importance of organizational strategies that cultivate supportive environments, including recognition, fair treatment, and adequate resource provision. Enhancing POS not only improves individual performance but also strengthens long-term organizational effectiveness. Therefore, managerial attention to employee needs and well-being is essential for maintaining competitiveness and achieving organizational objectives.